Nobody 2 [videorecording (Blu-Ray)] - Kolstad, Derek (Universal, 2025)
Workaholic assassin Hutch Mansell takes his family on a much-needed vacation to the small tourist town of Plummerville. However, he soon finds himself in the crosshairs of a corrupt theme-park operator, a shady sheriff, and a bloodthirsty crime boss. Good thing his whole family and his new dog have his back.